The Preterm Prediction Study: Association Of Caesarean Delivery With Increases In Maternal Weight And Body Mass Index - Mohamad, Norlia (2001)
Objectives: The purpose of this study was to evaluate whether maternal weight and body mass index measured before or during pregnancy are associated with an increased risk of caesarean delivery. This study also try to determine whether greater weight gain during pregnancy is associated with increased risk of caesarean delivery. Study design: This is a cross-sectional study conducted in the Obstetrics and Gynaecology Department, Hospital Universiti Sains Malaysia, Kubang Kerian Kelantan from 1 st August 1999 till 31 st July 2000. Candidates for this study are antenatal patient who came for booking and planned to deliver in HUSM with Singleton pregnancy at period of amenorrhoea of 32 weeks or less and their EDD must be before 31 st July 2000. During this one year 1359 pregnant women came for booking. Cases with multiple fetuses, stillbirth, fetal anomalies, selected medical and surgical complications, and those with incomplete medical record were excluded. 631 cases remained for analysis. Maternal weight and height were prospectively recorded. The prepregnancy weight was based on selfreporting and third trimester weight taken between 27 to 31 week. Both weight and height were used to calculate the body mass index, and its contribution to the risk of caesarean delivery was determined. XXIII Results: There is an increased in CS rate for prepregnancy maternal weight more than 79kg, OR=1.744(p=O.001). For third trimester weight more than 79kg, the odds ratio is 1.227 with p value of 0.002. Prepregnancy 8MI of 26.1-29, the odds ratio is 1.40B (p=0.08). Patients with prepregnancy BMI more than 29 have higher CS rate. The odds ratio is 3.042 (p=O.001). Third trimester 8MI of 26.1-29 gives an odds ratio of 1.291 (p=O.022). For third trimester 8MI more than 29, the odds ratio is 1.361 (p=O.014). Weight gain within 15.9-18.2kg is also associated with increased risk of es. The odds ratio is 4.225 (p=O.003). Greater weight gain(>1B.2kg) gives higher es rate, odds ratio is 4.331 (p=O.01). Univariate analysis of risk factors for caesarean delivery in 631 eligible women revealed an increased risk of caesarean section with maternal age less than 20 years and more than 39 years, OR=3.61 (p=0.027) and OR=2.S82(p=0.00S). Birth weight more than 4kg is also associated with higher rate of es. It gives odds ratio of ~.OOO (p<O.001). Multivariate stepwise logistic regression analysis confirmed the association of age, prepregnancy weight, prepregnancy 8MI, weight gain and baby birth weight as Significance variables contributing to caesarean delivery risk. Conclusion: The risk of es is associated with age, prepregnancy weight and 8MI, maternal weight gain and baby birth weight. Prepregnancy counselling about optimising maternal weight and monitoring weight gain during pregnancy to decrease risk of es are indicated by this study.